Understanding Why Railroad Yard Crews Run Through Misaligned Switches Through the Lens of Sociotechnical Systems. (September 2018) - Roth, Emilie M.; Multer, Jordan; France, Megan; Safar, Hadar; Grice, Rachel
We conducted a study to examine the factors that contribute to run through switches (RTS) in passenger rail yard operations. RTS occur when a train runs through a misaligned switch. It can result in damage to the switch that, if not detected and repaired, can increase the risk of derailment of a subsequent train coming in the opposite direction. The study was conducted at one passenger railroad and included interviews and focus groups with employees at different levels in the organization, as well as observations of yard operations. A sociotechnical systems perspective was used to identify physical infrastructure, individual, team and organizational contributors to RTS. This included performing a Systems Theoretic Process Analysis (STPA) to identify how interacting factors can lead to RTS. This paper provides a summary of the main results. It illustrates the value of adopting a sociotechnical lens when investigating safety incidents that involve human performance.